Consider the boundary value problem $$\varepsilon \frac{d^2y}{dx^2}+(1+x)\frac{dy}{dx}+y=0$$ subject to $y(0)=0$, $y(1)=1$, for $0 \leq x \leq 1$.

By considering the rescaling $x=x_0+\varepsilon ^{\alpha} X$ and $y=Y$,

for $X,Y=O(1)$ and $\alpha >1$, show that a boundary layer is only possible at $x=0$

So after rescaling, we have $$\varepsilon \frac{d^2y}{dx^2}+(1+x_0+\varepsilon ^{\alpha} X)\frac{dy}{dx}+Y=0$$

At leading order (when $\varepsilon =0$): $$(1+x_0+\varepsilon ^{\alpha} X)\frac{dy}{dx}+Y=0$$ which gives $$Y(1+x_0+\varepsilon ^{\alpha} X)=\frac{A_0}{1+x_0+\varepsilon ^{\alpha} X}$$

We have two boundary conditions. When $y(0)=0$ confuses me because then there would be a zero divider (so that must mean $y$ changes rapidly right?)

So what exactly do we do next to answer the question...

  • $\begingroup$ I can't write up an answer now, but take a look at the process in this answer, as well as the comments beneath it. $\endgroup$ – Antonio Vargas Nov 18 '15 at 0:40
  • $\begingroup$ @AntonioVargas Just had a look. It's quite confusing... In lectures they seemed to consider when epsilon is $0$ but in the link, it seems different. I think I might be misunderstanding. If you get time, please would you write something up. $\endgroup$ – snowman Nov 18 '15 at 0:44

You rescaled equation is incorrect, derivatives with respect to $x$ must also be transformed into derivative with respect to $X$. The easiest way to do this is with the chain rule, $$ \frac{dy}{dx}=\frac{dy}{dX}\frac{dX}{dx}=\epsilon^{-\alpha}\frac{dy}{dX}. $$

So your rescaled equation is $$\epsilon^{1-2\alpha}\frac{d^2Y}{dX^2}+(1+x_0+\epsilon^{\alpha}X)\epsilon^{-\alpha}\frac{dY}{dX}+Y=0, $$ or, separating powers of $\epsilon$, $$\epsilon^{1-2\alpha}\frac{d^2Y}{dX^2}+(1+x_0)\epsilon^{-\alpha}\frac{dY}{dX}+X\frac{dY}{dX}+Y=0. $$ Now, the $XY'(X)$ and $Y$ terms will be smaller than the $\epsilon^{1-2\alpha}$ and $\epsilon^{-\alpha}$ terms, so we need to balance $-\alpha$ and $1-2\alpha$, which means $\alpha=1$, and our leading order equation is $$ \frac{d^2Y}{dX^2}+(1+x_0)\frac{dY}{dX}=0. $$ The solution is $$Y=A\exp(-(1+x_0)X)+B$$ (this is the inner solution, or boundary layer solution). Now the inner solution should cannot grow exponentially out of a boundary layer, as if it did, you couldn't match it to the outer solution. This means you need the argument of $\exp$ ($-(1+x_0)X$) to be negative as $X$ goes out of the layer. If the layer is internal, you need $-(1+x_0)X=0$ as $|X|\rightarrow\infty$, if the layer is at the left end, you need $-(1+x_0)X<0$ as $X\rightarrow\infty$ and if the layer is at the right end of the interval, you need $-(1+x_0)X<0$ as $X\rightarrow-\infty$. Since $1+x_0\geq1$ we can only have a layer at the left end $x=0$.

The outer solution is what you get for $\epsilon=0$ in the unscaled equation, $$(1+x)\frac{dy}{dx}+y=\frac{d}{dx}\left((1+x)y\right)=0,$$ so $y=C/(x+1)$. If the boundary layer is at $x=0$ then the outer boundary condition is $y(1)=1$ so $C=2$.

To close the system you have to use matching conditions, $$\lim_{X\rightarrow\infty}Y(X)=\lim_{x\rightarrow0}y(x) $$ which gives $$\lim_{X\rightarrow\infty} A\left(e^{-X}-1\right)=2 $$ so $A=-2$ and $Y(X)=-2(e^{-X}+1)$. (Think about what would happen if we had $e^X$ instead of $e^{-X}$, this is why the layer had to be at $x=0$.)

And because they are always cool, here's the picture you get, for $\epsilon=0.1$, just to make sure. enter image description here

  • $\begingroup$ Nice exposition, especially the part about determining $x_0$. $\endgroup$ – Antonio Vargas Nov 18 '15 at 13:23
  • $\begingroup$ @David How did you get to $1+x_0 \geq 1$, how do you know that $x_0$ is nonnegative? $\endgroup$ – snowman Nov 18 '15 at 20:07
  • $\begingroup$ Because your domain is $0\leq x\leq 1$, if you have a boundary layer anywhere, it is between ) and 1, so $0\leq x_0\leq 1$. @AntonioVargas thanks, I think it's the first time I've really understood it properly myself, it was a good exercise to go through! $\endgroup$ – David Nov 18 '15 at 21:35
  • $\begingroup$ @David Thanks. There is a next part of the q which is: Use the method of matched asymptotic expansions to construct two-term inner and outer expansions to the problem, which should then be matched using Van Dyke's matching principle. The inner solution would be in terms of $x$ and $y$, $$y=B+Ae^{-\frac{x-x_0}{\varepsilon}}$$ but as epsilon tends to zero, it is $y=B$ right? $\endgroup$ – snowman Nov 19 '15 at 22:42
  • $\begingroup$ I got the outer solution as $$y=2(1+x)^{-1}+\varepsilon \bigg(\frac43(1+x)^{-4}-\frac16(1+x)^{-1} \bigg)$$ and this as terms of $X$ and $Y$ is $$Y=2(1+x_0+\varepsilon X)+\varepsilon \bigg(\frac43(1+x_0+\varepsilon X)^{-4}-\frac16(1+x_0 +\varepsilon X)^{-1} \bigg) +O(\varepsilon ^2)$$ and when you match these you get $B=2+2x_0$ right? Have I done it right? Can I have some help please. $\endgroup$ – snowman Nov 19 '15 at 22:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.